Effects of instrument-assisted soft tissue mobilization on muscle performance during vertical jump in young men - Corradi Afonso, André Augusto; Neves, Lucas Melo [UNESP]; Toscaro, Clenilson Gabriel; Gonçalves, Ronieder; Barrionuevo, Mario Luiz; de Oliveira, Edlene Perpétua; Domingues, Leonardo Casemiro; Neto, Luis Ferreira Monteiro; Braz, Igor Augusto; Jambassi Filho, José Claudio (Elsevier, 2025)
INTRODUCTION: Instrument assisted soft-tissue mobilization (IASTM) has become a popular myofascial intervention for sports medicine and rehabilitation professionals. The aim of the present study was to analyze the acute effects of IASTM on muscle performance measured by vertical jump height, peak power, and peak force. METHODS: Twenty-four young men were assigned to the IASTM or control sessions. The IASTM session was applied bilaterally to the quadriceps (rectus femoris, vastus lateralis, and vastus medialis), hamstrings (biceps femoris, semitendinosus, and semimembranosus), and triceps surae muscles (gastrocnemius and soleus). Each muscle region was mobilized for 60 s. During the control session, participants remained at rest for a similar total duration (∼15 min). Vertical jump assessments were performed pre-session and immediately, 24 h, and 48 h post-session. RESULTS: No significant Condition × Time interactions were observed between the IASTM and control sessions for jump height, peak power, or peak force (p > 0.05). CONCLUSION: The findings of the present study suggest that a single IASTM session does not produce significant changes in vertical jump height, peak power, or peak force immediately, or 24 and 48 h post-session in young men.